Kinds of unknowns and government linkages -empirical study of the application (Journal of the College of Education for Women, 2018)
It is no secret that the prophets speech is of great importance, as the second source of Islamic legislation after the Holy Quran, and as such we must reserve and verify the authenticity of the novel and the narrators seizure, and all the conditions laid down by the scholars.The subject of our research here concerns part of this verification, which is the unknown, the subject of the unknown hadith is considered a matter of great interest by the modernists because it relates to the validity of the novel and the narrators, and the methods of the modernists varied in terms of the reasons for this weakness, the fool never entertained them by the reckless narrative.I chose the subject of my research the types of Mahjail and the rule of its novel – an empirical study applied – to increase the information on the meaning of the unknown and types and criticism of the modern to the unknown and the reasons not to be adopted by modernists.This subject is broad and complex. It deals with the definition of the unknown and the rule of the unknown among the modernists, its types and the criticism of its innovators, the study of the subject followed the inductive method.